2001
DOI: 10.1002/jnr.1060
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mouse igf2 mRNA‐binding protein 3 and its implications for the developing central nervous system

Abstract: Functional analyses of neural RNA-binding proteins have focused mainly on their roles as modulators of posttranscriptional gene regulation, e.g., alternative splicing, dendritic mRNA localization, and local translation. Here we identified a mouse homologue of human IMP3, which is known to bind to and repress the translation of igf2 leader 3 mRNA. The mouse igf2 mRNA-binding protein 3 (mIMP3) is a member of the zipcode binding protein-1 (ZBP-1) family previously reported in chick fibroblast cells. mIMP3 was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 18 publications
8
45
0
Order By: Relevance
“…Although the fetal expression is prominent, data indicating that the proteins are also present in mature tissues have been accumulating (Mori et al 2001, Gu et al 2004. Adding to the previous data, we found that IMP1 mRNA was present in adult human kidneys, prostate, testis and ovaries, and IMP3 mRNA was found in brain, testis and ovaries, whereas IMP2 mRNA was more widespread but at low levels of expression.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although the fetal expression is prominent, data indicating that the proteins are also present in mature tissues have been accumulating (Mori et al 2001, Gu et al 2004. Adding to the previous data, we found that IMP1 mRNA was present in adult human kidneys, prostate, testis and ovaries, and IMP3 mRNA was found in brain, testis and ovaries, whereas IMP2 mRNA was more widespread but at low levels of expression.…”
Section: Discussionsupporting
confidence: 56%
“…Near the end of mouse embryogenesis IMP1 and IMP3 expression have almost disappeared (Mueller-Pillasch et al 1999. IMP1, IMP2 and IMP3 expression have, in general, not been reported in adult tissues, with a notable exception of the testis, where both IMP1 and IMP3 mRNAs have been described (Mori et al 2001, Wang et al 2003.…”
Section: Introductionmentioning
confidence: 96%
“…The early increase in Igf2 mRNA parallels the increase in neurons: both occur prior to the time at which let-7 levels normally rise, and both require the two conserved RNA-binding domains of LIN28. Igf2 has a documented role in the formation of neural tumors and promotes neurogenesis (Corcoran et al, 2008;Mori et al, 2001;Sim et al, 2006). Thus, the importance of Igf2 in neurogenesis is consistent with it being involved in the increase in neurons observed with constitutive LIN28.…”
Section: Research Articlementioning
confidence: 57%
“…In this way, they are involved in the temporal and spatial control of gene expression at the level of mRNA rather than at the level of gene transcription. The three mammalian VICKZ proteins (IMP1/CRD-BP, IMP2, and IMP3/KOC) are primarily expressed during embryonic development, and their expression is generally not detected in adult tissues, with the exception of placenta and testes (1)(2)(3)(4). In contrast, they are overexpressed in various cancers (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%